O05.3 The combined contraceptive vaginal ring increases Th17-related cytokines in the genital tract: a randomized crossover trial. (14th July 2019) - Konstantinus, Iyaloo; Balle, Christina; Jaumdally, Shameem; Gamieldien, Hoyam; Tanko, Ramla; Esra, Rachel; Happel, Anna-Ursula; Barnabas, Shaun; Gill, Katherine; Pidwell, Tanya; Maseko, Venessa; Myer, Landon; et al.
Abstract : Background: Progestin only-injections (NET-EN and DMPA) have been reported to increase HIV target cells in the female genital tract (FGT), which are target cells for HIV infection. Recently, CD4 Th17 cells have been identified to be more susceptible to HIV infection. Here, we investigated the impact of the combined contraceptive vaginal ring (CCVR, NuvaRing), combined oral contraceptive pills (COCPs) and NET-EN on Th17-related cytokines in the FGT of adolescent girls. Methods: This was a randomized crossover trial with a duration of 8 months. Adolescent girls between the ages of 15–19 were recruited and assigned to NET-EN, CCVR and COCPs in a 1:1:1 ratio. After four months, participants crossed over to another product for an additional four months. Cervical supernatants were collected at baseline, crossover and exit visits. Fifteen Th17-related cytokines were measured using Luminex multiplex assays. Results: A total of 130 participants were enrolled at baseline, with 107 reaching visit 2 (crossover) and 92 completing the final visit. Baseline characteristics were similar across arms. Median concentrations of Th17-related cytokine did not differ at baseline across all arms. In an intention to treat analysis (ITT) at crossover, intraindividual analysis of participants on CCVR showed an increase in IL-21 (p = 0.009), IL-1β (p = 0.007), TNF-α (p = 0.01) and IFN-γ (p = 0.016). We did not see any intraindividual differences within the NET-EN and COCPs arm. Comparison across arms at both crossover and exit showed elevated Th17-related cytokines (including IL-17A, IL-6, IL-1β, IL-33, TNF-α) in participants on CCVR compared to those on NET-EN and COCPs. Conclusion: In summary, the use of CCVR was associated with an increase in Th17-related cytokines compared to NET-EN and COCPs. Further studies are needed to investigate how these immune alterations in the FGT contribute to HIV risk in adolescent girls. Disclosure: No significant relationships.